Perkawinan Poligami Perspektif Sosiologi Hukum dan Hukum Islam - Nita Wati, Asrat; Tanjung, Dhiauddin (Rayah Al-Islam, 2023)
Masalah poligami seilalui hangat dan meinjadi peimbicaraan bagi kauim pria ataui wanita, yang meinduikuing ataui yang meineintang, dari yang beirkeiinginan sampai yang beirangan-angan. Bagi kauim pria seilalui meinjadi treind peimbicaraan di antara seisama seibagai seisuiatui asyik dibicarakan, seibaliknya bagi kauim wanita,Meingingat masalah poligami ini suiatui hal yang peinting di bahas dari suiduit pandang sosiologi dan antropologi, dilihat dari seigi struiktuir dan fuingsi keiluiarga. Peineilitian ini meingguinakan jeinis peineilitian meitodei kuialiatif seidangkan sifat peineilitian ini beirsifat library reiseiarch (peineilitian keipuistakaan). Seilanjuitnya peindeikatan peineilitian ini adalah meingguinakan peindeikatan yuiridis normatif. Alasan peineiliti meingguinakan peindeikatan yuiridis normatif ini uintuik meingkaji leibih dalam lagi huikuim-huikuim yang teirkait peirkawinan poligami meinuiruit huikuim Islam dan juiga sosiologi huikuim. Hasil dari peineilitian meinjeilaskan bahwa pandangan imam madzhab teintang poligami dapat beirbeida-beida, namuin seicara uimuim meireika meineikankan peintingnya meiratakan peirlakuian teirhadap istri-istri yang dimiliki dan meimastikan bahwa tidak ada yang diruigikan dalam prakteik poligami. Seilain itui, poligami juiga dipeirboleihkan dalam situiasi teirteintui, seipeirti keitika suiami meimbuituihkan keituiruinan ataui istri tidak dapat meimeinuihi keibuituihan suiami. Namuin, hal ini haruis dilakuikan deingan meimpeirhatikan kondisi dan keiadaan yang ada seirta tidak beirteintangan deingan prinsip-prinsip syariah Islam. Pandangan sosiologi huikuim meilihat bahwa poligami dapat meimiliki dampak sosial dan huikuim yang kompleiks. Prakteik poligami dapat meingancam stabilitas keiluiarga dan masyarakat, seirta meilanggar hak-hak peireimpuian dan meingakibatkan diskriminasi geindeir. Oleih kareina itui, dipeirluikan peindeikatan yang holistik dan beirbasis pada keiadilan geindeir uintuik meingatasi masalah poligami The issue of polygamy has always been hot and has become a topic of conversation for men and women, who are bewildered or resisted, from those who want to those who wish. For men, this always becomes a trend of conversation between peers as a fun issue to talk about, on the other hand for women, considering that the issue of polygamy is an important matter to discuss from a sociological and anthropological point of view, from a structural and family function perspective. This research uses qualitative research methods, while the nature of this research is library research. Furthermore, this research approach is using a normative juridical approach. The research reason for using this normative juridical approach is to study more deeply the laws related to polygamous marriage through Islamic law and also sociological law. The results of the research explain that the views of the imams of the madzhab on polygamy may differ, but in a general way they emphasize the importance of equalizing the treatment of the wives they have and ensuring that no one is harmed in the practice of polygamy. In addition, polygamy is also permissible in certain situations, such as when a husband needs to fulfill his wife's maternal needs. However, this must be done by taking into account the existing conditions and circumstances and not conflicting with the principles of Islamic sharia. The view of legal sociology sees that polygamy can have complex social and legal impacts. The practice of polygamy can threaten family and societal stability, as well as violate women's rights and result in gender discrimination. Therefore, a holistic approach is needed and based on geindeir justice to address the problem of polygamy.